Using Bibliometric and Social Media Analyses to Explore the "Echo Chamber" Hypothesis. (March 2014) - Goldie, David; Linick, Matthew; Jabbar, Huriya; Lubienski, Christopher
Educational policy debates are no longer occurring exclusively in academic or governmental settings. Intermediary actors are promoting research using a variety of traditional and non-traditional media to advance and oppose policy agendas. Given the current policy arena, it is useful to re-examine the research underlying current reforms, and to determine whether there is an "echo-chamber" effect, where a small, or unrepresentative, sample of studies is repeatedly cited to create momentum around a policy proposal. In exploring the echo-chamber hypothesis, we focus on two distinct methodologies. Using bibliometric methods and examining social media activity by intermediary organizations, our preliminary evidence suggests the presence of an echo-chamber effect in policy debates.